2023
DOI: 10.1037/tra0001263
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and posttraumatic stress disorder among Venezuelan migrants in Colombia and the United States: The moderating effect of gender.

Abstract: Objectives: The primary aim of this study was to examine the association between perceived discrimination and posttraumatic stress disorder (PTSD) outcomes among recently arrived Venezuelan parents in Florida and Colombia. The secondary aim was to determine whether, given the existence of an association between perceived discrimination and PTSD, this association may have been moderated by gender or by country of relocation. This is the first study to examine perceived discrimination and PTSD in Venezuelan migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Whereas prior research has documented the deleterious effect of migration-related cultural stress on behavioral health in general and PTSD in particular (S. J. Schwartz et al, 2018; Vos et al, 2022), fewer studies have done so while accounting for exposure to natural disasters or severe premigration trauma (LeMaster et al, 2018). These findings not only shed light on the experiences of Puerto Rican Maria migrants; they also raise questions as to the impact of cultural stressors among other Latin American immigrant groups exposed to high levels of stress or trauma in their premigration contexts—that is, crisis migrants relocated after Venezuela’s inflationary/social crises or El Salvador’s crises related to gang violence (Salas-Wright et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas prior research has documented the deleterious effect of migration-related cultural stress on behavioral health in general and PTSD in particular (S. J. Schwartz et al, 2018; Vos et al, 2022), fewer studies have done so while accounting for exposure to natural disasters or severe premigration trauma (LeMaster et al, 2018). These findings not only shed light on the experiences of Puerto Rican Maria migrants; they also raise questions as to the impact of cultural stressors among other Latin American immigrant groups exposed to high levels of stress or trauma in their premigration contexts—that is, crisis migrants relocated after Venezuela’s inflationary/social crises or El Salvador’s crises related to gang violence (Salas-Wright et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although Puerto Ricans are U.S. citizens, prior research has made clear that, upon relocation to the mainland, many island-born Puerto Ricans experience interpersonal and social marginalization on the basis of their Hispanic identity and, in many cases, due to limited or nonnative English proficiency (Aranda & Rivera, 2016; Szalacha et al, 2003). Rooted in cultural stress theory, prior research has found that exposure to migration-related cultural stressors is related to psychological distress and specifically to PTSD symptom severity (Salas-Wright & Schwartz, 2019; Vos et al, 2022). The link between cultural stress exposure and trauma response is in keeping with theory and empirical findings indicating that identity-based discrimination and social rejection can produce traumatic reactions by means of acute and chronic/cumulative exposure, or a combination of both exposure types (Carter, 2007; Carter et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are likely multiple reasons for this, one potential explanation involves the potential predictive link between hurricane stress and cultural stress. Two cross-sectional studies conducted by our research group, one with Hurricane Maria survivors on the U.S. mainland (Schwartz et al, 2022) and another with Venezuelan immigrants in Colombia and the United States (Vos et al, 2022), have found that premigration crisis-related stressors may predict postmigration cultural stress. Although the research designs used in these studies do not permit us to draw directional conclusions, the hypothesis suggested by these two sets of findings—in two different populations—is that stressors occurring prior to migration, and that may have helped to prompt the migration, may predispose individuals toward experiencing or perceiving cultural stress in the destination country or region.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study contributes to the nascent but growing research on Venezuelan migrants’ psychological well-being. Previous studies found that Venezuelan immigrants experience psychological distress due to societal discrimination [ 61 , 62 , 63 , 64 ], fears about education and career status loss in the destination country [ 65 ], and the COVID-19 pandemic in general [ 23 ]. Moreover, there is evidence that Venezuelans in Peru experience stress when unable to send remittances during the pandemic [ 66 ].…”
Section: Discussionmentioning
confidence: 99%